2016
DOI: 10.1061/(asce)cp.1943-5487.0000595
|View full text |Cite
|
Sign up to set email alerts
|

Peak Shear Strength of Discrete Fiber-Reinforced Soils Computed by Machine Learning and Metaensemble Methods

Abstract: The accuracy of prior theoretical and empirical models for predicting the shear strength of fiber-reinforced soil (FRS) is questionable because of the difficulty of using these simplified models to describe the complex mechanism of soil-fiber interaction. This study compiled a large database of available high quality triaxial and direct shear tests on FRS documented in the literature from 1983 to 2015. The database includes information on the properties of sand, fibers, soil-fiber interface, and stress paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 62 publications
(116 reference statements)
0
31
0
Order By: Relevance
“…AdaBoost Advances in Civil Engineering ensemble of CTrees can be defined as a combination of multiple CTrees in which the final prediction result is obtained by combining the outputs of individual trees. Based on previous works [52][53][54][55][56], ensemble models have demonstrated better performance than individual models in a wide range of applications. e AdaBoost algorithm is demonstrated in Figure 6.…”
Section: Adaptive Boosting Classificationmentioning
confidence: 99%
“…AdaBoost Advances in Civil Engineering ensemble of CTrees can be defined as a combination of multiple CTrees in which the final prediction result is obtained by combining the outputs of individual trees. Based on previous works [52][53][54][55][56], ensemble models have demonstrated better performance than individual models in a wide range of applications. e AdaBoost algorithm is demonstrated in Figure 6.…”
Section: Adaptive Boosting Classificationmentioning
confidence: 99%
“…ANNs, although not new, they are supported in a strong background and experience. Indeed, they have been applied in the past with high success in different knowledge domains including in civil engineering (Chou et al 2016, Gomes Correia et al 2013). There are also some examples of ANNs applications in slope stability analysis (Wang et al 2005, Cheng et al 2012.…”
Section: Modelingmentioning
confidence: 99%
“…As for the shear strength, many scholars showed the applicability of intelligent models. Chou et al [25] showed the efficiency (correlation coefficient (R) = 0.89 and mean absolute percentage error (MAPE) = 3.27%) of machine learning for computing peak shear strength of discrete fiber-reinforced soils. Havaee et al [26] used a multiple linear regression (MLR) model to predict the shear strength in the central part of Iran.…”
Section: Introductionmentioning
confidence: 99%